BINDING OF PARACOCCIDIOIDES-BRASILIENSIS TO LAMININ THROUGH SURFACE GLYCOPROTEIN GP43 LEADS TO ENHANCEMENT OF FUNGAL PATHOGENESIS - Vicentini, A. P.; Gesztesi, J. L.; Franco, M. F.; Desouza, W.; Demoraes, J. Z.; Travassos, L. R.; Lopes, J. D. (Amer Soc Microbiology, 1994)
Extracellular matrix protein laminin binds specifically to yeast forms of Paracoccidioides brasiliensis and enhances adhesion of the fungus to the surface of epithelial Madin-Darby canine kidney cells in vitro. Immunoblotting of fungal extracts showed that the gp43 glycoprotein is responsible for adhesion. This was confirmed by binding assays using purified gp43, with a K-d of 3.7 nM. The coating of P. brasiliensis yeast forms with laminin before injection into hamster testicles enhanced the fungus virulence, resulting in a faster and more severe granulomatous disease. These results indicate that interaction of fungi with extracellular matrix elements may constitute a basis for the evolution of fungal infection toward regional spreading and dissemination.